Pengaruh Pemberian LKS Latihan Soal Terstruktur Terhadap Pemahaman Konsep Isomer Senyawa Hidrokarbon Pada Siswa Kelas XI IPA SMA Negeri 4 Palangka Raya Tahun Ajaran 2018/2019 - Corry Anggraini; Abudarin Abudarin; Nopriawan Berkat Asi (Jurnal Ilmiah Kanderang Tingang, 2020)
The purpose of this study was to describe the effect of providing structured question worksheet on the understanding of the concept of isomeric hydrocarbon compounds in class XI-IPA students of SMA Negeri 4 Palangka Raya in the 2018/2019 school year. This study was an experimental study with a Pretest Posttest Control Group Design research design and involved 56 students from two classes XI IPA of SMA Negeri 4 Palangka Raya as a sample determined by the cluster random sampling technique, namely students of class XI IPA-1 (experimental class) as many as 29 students and students of class XI IPA-2 (control class) were 27 students. The instrument used was in the form of C-1 concept comprehension test questions contained in test I, test II, LKS structured practice questions and LKS practice questions. Test I data is obtained after direct learning and Test II data is obtained after learning using the LKS structured practice questions and the LKS practice questions. The results showed that the administration of structured question worksheets affected the understanding of the concept of the isomer of hydrocarbon compounds in the lower class students of Class XI IPA of SMA Negeri 4 Palangka Raya in 2018/2019 school year. The average conceptual understanding of experimental class students (85.60) is higher than the control class (59.25). Worksheet structured questions give effect to lower group students and upper group students.